Prevalence of primary drug resistance to rifampicin and isoniazid in newly diagnosed sputum smear positive pulmonary Tuberculosis - Kumar, Ashok; Joshi, Jawahar Lal; Umathoor, Abdurazack; Chopra, Vishal; Kaur, Komaldeep; Mittal, Vidhu (International Journal of Research in Medical Sciences, 2019)
Background: To determine the prevalence of primary drug resistance to either rifampicin or isoniazid alone or both in newly diagnosed sputum smear positive pulmonary tuberculosis patients. Method: A prospective study 100 newly diagnosed sputum smear positive pulmonary TB patients was conducted. The patients with an age of ≥15 years and who had either not taken anti TB treatment or who had taken ATT for less than 1 month were enrolled in this study. Two sputum samples (5ml each), including one early morning sample as per the RNTCP guidelines were collected and subjected to line probe assay (LPA). Results: Out of 100 cases 6 were having resistance to both rifampicin and isoniazid, 9 has resistance to INH alone and 1 had resistance to rifampicin alone. Conclusion: The prevalence of primary drug resistance is high. For early and rapid detection of DR-TB newer modality should be used for the detection of primary drug resistance in sputum smear positive TB patients.